Functional outcomes of acromioclavicular joint dislocation repair using the double Endobutton technique: a retrospective study - Bansal, Aakash; Meena, R. P.; Singh, Prince; Meena, Umesh Kumar; Kharalwa, Rohit (International Journal of Research in Orthopaedics, 2025)
Background: A range of surgical techniques has been proposed for acromioclavicular (AC) joint dislocations. Traditional methods, including hardware fixation and non-anatomical reconstructions, are often associated with complications and high failure rates. Recent advancements focus on anatomical reconstruction of the coracoclavicular (CC) ligaments to improve outcomes. This study evaluates the clinical and radiological results of the double Endobutton technique, which reconstructs the trapezoid and conoid ligaments separately, in acute complete AC joint dislocations. Methods: A retrospective study was conducted at government medical college, Kota, from December 2022 to December 2024, involving 40 patients with Rockwood type III to V injuries. Reconstruction was performed using double Endobuttons, Mersilene tape, and 5 Ethibond sutures through a vertical strap incision. The cohort comprised 18 type V, 6 type IV, and 5 type III injuries; 12 right-sided and 28 left-sided. Results: Outcomes were assessed using the Constant score and disabilities of the arm, shoulder and hand (DASH) questionnaire at 6, 12, and 24 weeks postoperatively, along with radiological evaluations via Zanca and bilateral AP stress views. At final follow-up (mean: 12 months; range: 8-14), 36 patients had excellent outcomes, 2 had good, and 2 had fair results. The mean Constant score was 96 (range: 80-100) and the mean DASH score was 5.3 (range: 1-11). Conclusions: The double endobutton technique offers favorable clinical and radiological outcomes, with effective anatomical reduction and functional restoration in most patients. It is a safe and reliable option for treating complete AC joint dislocations.